(NbIBLIOTEKA (BXXI (NWEKA (B:s [(NsBORNIK (B: (NpER(B. (NS POL(B.] /s - (NlEM(B, (NsTANISLAWs ((NmOSKWA (B:s (NiZD(B-(NWO ast(B,s, 2003)
(Nw SBORNIK WO[LI PROIZWEDENIQ (B("(NaBSOL@TNAQ PUSTOTA(B", "(NrOBINZONADY(B", "(NgIGAME[(B", "(NsEKSOTRQSENIE(B" (NI DRUGIE(B) (NFILOSOFSKIE(B, (NZABAWNYE(B, (NBESKONE^NO ORIGINALXNYE (B- (NI(B, (NPO(B-(NLEMOWSKI(B, (NNEPODRAVAEMO OSTROUMNYE(B. (NdLQ [IROKOGO KRUGA ^ITATELEJ(B.s
Keywords: (NlITERATURNYE APOKRIFYs; (NfILOLOGI^ESKIE NAUKIs -- (NhUDOVESTWENNAQ LITERATURAs -- (NpOLX[As; (NhUDOVESTWENNAQ PROZAs -- (No^ERKI O LITERATURE I ISKUSSTWEs -- (NfILOSOFSKO(B-(N\STETI^ESKIE O^ERKIs; (NpOLXSKAQ LITERATURAs -- 1945 (NG(B.s -- (NpROIZWEDENIQ HUDOVESTWENNOJ LITERATURYs